Characterization of nanocellulose from banana stem fiber and its bionanocomposite as a thermal insulation material - A.I. Syahrul; M.D. Rosyidin; S. Hidayat; K. Khaerunisa; N. Soraya; N.H. Sari; S. Syahrul (Universitas Mataram, 2025)
Nanocellulose has garnered significant attention due to its unique properties and potential in various applications, including thermal insulation. The abundant banana stems found in Lombok Island generate considerable waste that can be utilized as a raw material for nanocellulose. This research aims to characterization of nanocellulose derived from Kepok banana stems and its composites as thermal insulation in solar panels. Nanocellulose was produced using acid hydrolysis with sulfuric acid (H2SO4), and several treatments were carried out including Natrium hydroxide (NaOH), Sodium chlorite (NaClO2), Sulfuric acid (HÃ‚Â2SO4), The results show that nanocellulose from banana stems has a tensile strength of 13.374 MPa - 13.63 MPa. The addition of nanocellulose was found to increase the tensile strength of the composite reaching 13.374 up to 13.63 MPa, thermal conductivity 0,1692 up to 0,1940 W/mK and is quite heat resistant at a temperature of 200 Ã‚Â°C. SEM photos of nanocellulose show surface roughness and produce interface strength between banana stem fiber nanocellulose and polyester resin. With solid bonding, good tensile strength, conductivity and thermal stability, bionancomposites from banana stem can be used as thermal insulator (backsheet) materials for solar panels.